2006
DOI: 10.1080/01485010500428389
|View full text |Cite
|
Sign up to set email alerts
|

High Inguinal Loupe-Assisted Varicocelectomy for Subfertile Men With Varicococeles: Technical Feasibility, Clinical Outcomes and Complications

Abstract: & 254 consecutive patients underwent high inguinal loupe-assisted varicocelectomy. All patients had at least a one year history of infertility with abnormal semen parameters and physical examination and=or color Doppler ultrasound proven varicocele. To facilitate the procedure, an Â3.0 loupe was used during spermatic cord dissection near or at level of internal inguinal ring. Semen analysis and physical examination were performed at 3 monthly intervals. No intra-operative complications occurred. The most commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Comparing the results of varicocelectomy from different studies, Hsieh et al . demonstrated a significant increase in sperm concentration and sperm forward motility, as well as a 37% pregnancy rate 33 . The present study also showed an improved semen result in 1815 patients (86.7%), with 1184 patients’ (56.6%) converting to normal in sperm concentration and motility.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Comparing the results of varicocelectomy from different studies, Hsieh et al . demonstrated a significant increase in sperm concentration and sperm forward motility, as well as a 37% pregnancy rate 33 . The present study also showed an improved semen result in 1815 patients (86.7%), with 1184 patients’ (56.6%) converting to normal in sperm concentration and motility.…”
Section: Discussionmentioning
confidence: 94%
“…Hsieh et al . performed high inguinal loupe-assisted varicocelectomy in 254 cases, revealing a palpable recurrence rate of 3.1% 33 . In patients who underwent MIMV, the recurrence rate, as determined using results of physical examination and/or color Doppler ultrasound, was 0.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Again, Abdelrahman et al [16] reported that they achieved more significant improvement in the concentration and motility with the loupe varicocelectomy compared to the non-microscopic varicocelectomy group. In another study, in which the results of loupe-assisted varicocelectomy were shared, the increase in motility was reported to be 46% and the mean sperm concentration was 17 X 10 6 /mL (24 -41 X 10 6 /mL) [17]. In another study in which the results of microscopic varicocelectomy were reported, the rate of pregnancy was 55%, improvement in sperm concentration was 22%, motile A + B was 59%, and normal morphology ratio was 51% [18].…”
Section: Discussionmentioning
confidence: 98%
“…One study that was conducted on a smaller number of cases ( n = 26) showed significant intraoperative anatomical differences between the two techniques, but they neither occluded the spermatic cord nor delivered the testis [9] . Classical LV has proven its efficacy in multiple studies, especially when it was compared to classic open techniques [10] , [11] , [12] .…”
Section: Discussionmentioning
confidence: 99%